Genotype-phenotype pattern analysis of pathogenic PAX9 variants in Chinese Han families with non-syndromic oligodontia - Ren, Jiabao; Gan, Sifang; Zheng, Shushen; Li, Meikang; An, Yilin; Yuan, Shuo; Gu, Xiuge; Zhang, Li; Hou, Yan; Du, Qingqing; Zhang, Guozhong; Shen, Wenjing (Frontiers in Genetics, 2023)
Background: Non-syndromic oligodontia is characterized by the absence of six or more permanent teeth, excluding third molars, and can have aesthetic, masticatory, and psychological consequences. Previous studies have shown that PAX9 is associated with autosomal dominant forms of oligodontia but the precise molecular mechanisms are still unknown. Methods: Whole-exome and Sanger sequencing were performed on a cohort of approximately 28 probands with NSO, for mutation analysis. Bioinformatic analysis was performed on the potential variants. Immunofluorescence assay, western blotting, and qPCR were used to explore the preliminary functional impact of the variant PAX9 proteins. We reviewed PAX9-related NSO articles in PubMed to analyze the genotype-phenotype correlations. Results: We identified three novel PAX9 variants in Chinese Han families: c.152G>T (p.Gly51Val), c.239delC (p.Thr82Profs*3), and c.C409T (q.Gln137X). In addition, two previously reported missense variants were identified: c.140G>C(p.Arg47Pro) and c.146C>T (p.Ser49Leu) (reference sequence NM_006194.4). Structural modeling revealed that all missense variants resided in the highly conserved paired domain. The other variants led to premature termination of the protein, causing structural impairment of the PAX9 protein. Immunofluorescence assay showed abnormal subcellular localizations of the missense variants. In human dental pulp stem cells, western blotting and qPCR showed decreased expression of PAX9 variants compared with the wild-type group at both the transcription and translation levels. A review of published papers identified 64 PAX9 variants related to NSO and found that the most dominant feature was the high incidence of missing upper second molars, first molars, second premolars, and lower second molars. Conclusion: Three novel PAX9 variants were identified in Chinese Han families with NSO. These results extend the variant spectrum of PAX9 and provide a foundation for genetic diagnosis and counseling.